The Future of Transportation. Modifications are Needed to Be Done – EU View - Tuparova, Stela (Research Papers, 2024)
The current research is aimed at analyzing the urgent need for transport changes which are needed to happen in the upcoming years. Continuously growing globalization puts transport in front the need of high-quality requirements of a diverse nature. Achieving high energy efficiency, decarbonization, minimizing costs, increasing profits, customers’ satisfaction are among the main goals which the sector sets for improvement. Optimizations and digitalization become leading levers for successful adaptation of the transport sector to the constantly changing external conditions and environment. Strategic documents related to the dynamics of economic situation both in Europe and on the world scene had been studied and analyzed for the purpose of the research.